A new hybrid actuation scheme with artificial pneumatic muscles and a magnetic particle brake for safe human–robot collaboration. (April 2014) - Shin, Dongjun; Yeh, Xiyang; Khatib, Oussama
Interest in the field of human-centered robotics continues to grow, particularly in utilizing pneumatic artificial muscles (PAMs) for close human–robot collaborations. Addressing the limited control performance of PAMs, we proposed a hybrid actuation scheme that combines PAMs (macro) and a low-inertia DC motor (mini). While the scheme has shown significantly improved control performance and robot safety, a small DC motor has difficulties in handling the large stored energies of the PAMs, particularly for large changes in initial load due to PAM failure. In order to further improve robot safety, we develop a new hybrid actuation scheme with PAMs (macro) and a particle brake (mini). This design allows for a higher torque-to-weight ratio and inherently stable energy dissipation. Addressing optimal mini actuation selection between a motor and a brake, and a control strategy for PAMs and a brake, we conducted comparative studies of hybrid actuations with (1) a DC motor and (2) a brake for concept validation. Experimental comparisons show that the hybrid actuation with PAMs and a brake provides higher energy efficiency for control bandwidths under 2 Hz, and more effective reduction of large impact forces due to the brake's high torque capacity and passive energy dissipation.